Omnidirectional Circularly Polarized Monopole Antennas on Artificial Magnetic Conductor Ground Plane - Pisit Janpangngern; Ryuji Kuse; Chuwong Phongcharoenpanich; Takeshi Fukusako (My University, 2024)
This research proposes omnidirectional circularly polarized monopole antennas (OCPA) with single-annular (SA-AMC) and dual-annular artificial magnetic conductor (DA-AMC) ground planes. The aim of the proposed antenna scheme is to circumvent the design rigidity of conventional OCPA whose inherent shortcoming is fixed bottom ground plane size. The OCPA with SA-AMC ground plane consists of a monopole element, four diagonally adjoined parasitic elements to covert linear to circular polarizations, and an SA-AMC ground plane. The OCPA with DA-AMC ground plane consists of a monopole element, four diagonally adjoined parasitic elements, and a DA-AMC ground plane. Unlike the conventional OCPA, the bottom ground plane radius ( R g ) of the OCPA with SA- and DA-AMC ground planes can be varied between 18.4 – 188.4 mm; and 29.2 – 119.2 mm, respectively, without affecting the omnidirectionality and impedance and axial ratio (AR) bandwidths of the OCPA. Furthermore, the SA- and DA-AMC ground planes effectively improve the impedance (| S 11 | ≤ –10 dB) and AR bandwidths (AR ≤ 3 dB) while reducing leakage current on the coaxial feeder cable. The measured | S 11 | and AR bandwidths of the OCPA with SA-AMC ground plane, given the optimal Rg of 18.4 mm, are 8.08% (5.34 – 5.79 GHz) and 4.38% (5.36 – 5.60 GHz), while those of the OCPA with DA-AMC ground plane, given the optimal R g of 29.2 mm, are 14.37% (5.10 – 5.89 GHz) and 19.85% (4.90 – 5.98 GHz). The novelty of this research lies in the use of SA- and DA-AMC structures to circumvent the design rigidity of the conventional OCPA. Essentially, the integration of the AMC structures offers design flexibility in the realization of OCPA.
Keywords: Ground plane; Helical antenna; Antenna Design and Analysis